Event-triggered active disturbance rejection control for a class of networked systems with unmatched uncertainties: Theoretic and experimental results. (October 2021) - Cui, Kaixin; Tang, Shu-Xia; Huang, Yuan; Yu, Hao; Shi, Dawei
Abstract: In this work, an event-triggered control problem for a class of networked systems with unmatched uncertainties is investigated based on an active disturbance rejection control approach. To estimate the effect of unmatched uncertainties, a bank of extended state observers with guaranteed convergence is proposed. Based on the obtained estimates, a tracking-differentiator-enabled Zeno-free event-triggering condition is introduced with reduced sampling cost. An event-triggered controller is then designed to guarantee the closed-loop stability of the networked system with unmatched uncertainties, leveraging a backstepping control approach. Implementation issues of the proposed approach are discussed, and the effectiveness of the results is illustrated through experimental results on a DC torque motor platform.